Effect of Land Use Intensity On Diversity And Abundance of Soil Insects And Earthworms In Sumberjaya, Lampung - F.K Aini, F.K Aini (Universitas Jambi, 2009)
Insects, including termites, ants, and beetles are taxonomically diverse, abundant, andecologically important in the soil environment. Although not too diverse, earthworms are also abundantin the soil. The objective of this study was to determine the effect of land use (LU) change on diversityand abundance of soil insects and earthworms in Sumberjaya, Lampung. Methods used were monolith(for earthworms), transect (for termites), and Winkler (for ants and beetles). Termites and earthwormswere identified up to species, ants up to generic level, and beetles to family/sub-family level. Resultsshow that from seven land use types (less disturbed forest, more disturbed forest, polyculture coffee,monoculture coffee, food crop, vegetable crop, and shrub) we found 53 ant genera, 59 beetle families/ subfamilies, 37 termite species, and 10 earthworm species. Diversity and abundance of ants,beetles, and termites decrease as LU intensity increases. LU change did not affect earthwormdiversity or abundance, but smaller-sized earthworms tended to be found in more intensive LU types.Deforestation caused the loss of native earthworm species.